A Study of Arabic Textbooks for Madrasah Tsanawiyah - Oktafatricia, Eva; Aslamiyah, Suwaybatul; Syahrir, Sultan; Amiruddin, Amiruddin (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2022)
Textbooks must meet the criteria for appropriate textbooks that have been set by BSNP, so that the teaching materials in them are quality teaching materials. The purpose of this study was to analyze the Arabic language textbook for class VIII that was published by Erlangga whether the textbooks have met BSNP standards and has met the quality of textbooks based on aspects of material, presentation, language and graphics. This type of research was content analysis research, which aimed to analyze more deeply the content of Arabic textbooks for the class VIII in Madrasah Tsanawiyah. The approach used in this research was a qualitative approach. The method used was the study of documentation and literature study. According the results of this study, Arabic textbooks for class VIII published by Erlangga are books that were not fully in accordance with BSNP standards and meet the quality of teaching materials based on material, presentation, linguistic, and graphic aspects. Based on the study, it could be concluded that this Arabic book was worthy of being used as a handbook based on its advantages. A prominent weakness of this book was from the aspect of graphic presentation.